High Growth Firms in Low Trust Environments - an Empirical Study - Latusek-Jurczak, Dominika (Studia Oeconomica Posnaniensia, 2017)
According to existing studies, high growth enterprises flourish mainly in high trust societies. The article presents a qualitative study conducted among successful start-ups in Poland, where the level of social trust is extremely low.